Clivagem e construções similares: contraste, foco e ênfase - Pezatti, Erotilde Goreti [UNESP] (My University, 2012)
This paper deals with so called cleft constructions and other similar structures in eight Portuguese varieties, aiming to show that the formal differences correspond to different functional strategies used by the Speaker to achieve his/her communicative intentions, i.e., Focus, Contrast and Emphasis, in accordance with the theory of Functional Discourse Grammar (Hengeveld and Mackenzie, 2008). This study takes as evidence real spoken occurrences extracted from a corpus organized by Linguistic Centre at the University of Lisbon, in partnership with the University of Toulousse Mirail and the University of Provence-Aix-Marseille. The results show the following distribution: cleft construction is a strategy for pragmatic function Contrast marking; Focus-ser constructions are used to highlight a constituent and (é) que is used as an operator of emphasis showing the speaker’s desire to intensify certain pieces of information.

Este estudo trata de estruturas denominadas clivagem ou construções-(é)que, em oito variedades portuguesas, objetivando mostrar que as diferenças formais correspondem a diferentes estratégias utilizadas pelo Falante para atingir seus objetivos comunicativos, ou seja, Foco, Contraste e Ênfase, de acordo com a teoria da Gramática Discursivo-Funcional (Hengeveld e Mackenzie, 2008). Para isso toma como material de análise ocorrências reais de uso extraídas do corpus oral organizado pelo Centro de Linguística da Universidade de Lisboa, em parceria com a Universidade de Toulouse-le-Mirail e a Universidade de Provença-Aix-Marselha. A análise dos dados lusófonos revela que clivagem constitui uma estratégia de marcação da função pragmática Contraste; construções de Foco-Ser, por outro lado, são usadas para focalizar um constituinte; (é) que, por sua vez, constitui um operador de Ênfase, já que assinala o desejo do Falante de intensificar partes de informação.
Cleft constructions and similar structures: contrast, focus and emphasis
Keywords: Lusofonia; Clivagem; Foco; Ênfase; Contraste; varieties of Portuguese; cleft constructions; focus; contrast; emphasis